The Frequency of Nonmotor Symptoms among Advanced Parkinson Patients May Depend on Instrument Used for Assessment - Nelson Hwynn; Ihtsham U. Haq; Irene A. Malaty; Andrew S. Resnick; Michael S. Okun; Danica S. Carew; Genko Oyama; Yunfeng Dai; Samuel S. Wu; Ramon L. Rodriguez; Charles E. Jacobson; Hubert H. Fernandez (Parkinson's Disease)
Background. Nonmotor symptoms (NMS) of Parkinson's disease (PD) may be more debilitating than motor symptoms. The purpose of this study was to determine the frequency and corecognition of NMS among our advanced PD cohort (patients considered for deep brain stimulation (DBS)) and caregivers. Methods. NMS-Questionnaire (NMS-Q), a self-administered screening questionnaire, and NMS Assessment-Scale (NMS-S), a clinician-administered scale, were administered to PD patients and caregivers. Results. We enrolled 33 PD patients (23 males, 10 females) and caregivers. The most frequent NMS among patients using NMS-Q were gastrointestinal (87.9%), sleep (84.9%), and urinary (72.7%), while the most frequent symptoms using NMS-S were sleep (90.9%), gastrointestinal (75.8%), and mood (75.8%). Patient/caregiver scoring correlations for NMS-Q and NMS-S were 0.670 (𝑃<0.0001) and 0.527 (𝑃=0.0016), respectively. Conclusion The frequency of NMS among advanced PD patients and correlation between patients and caregivers varied with the instrument used. The overall correlation between patient and caregiver was greater with NMS-Q than NMS-S.